Market Orientation and Performance of Small Businesses in South Africa - Agbobli, Edem Korku; Oni, Olabanji; Fatoki, Olawale (Journal of Economics and Behavioral Studies, 2017)
The study focused on identifying the relationship between market orientation and performance of small businesses in Vryburg region of South Africa. It aimed to achieve the following objectives, (1) To determine the level of market orientation among small businesses in Vryburg region of South Africa, (2) To establish if there is any relationship between market orientation and performance of small businesses in Vryburg region of South Africa. The study was exploratory in nature and utilised the quantitative research method with a descriptive research design. 268 questionnaires were distributed to small businesses owners/managers in the Vryburg region of South Africa. 207 questionnaires were returned, 9 questionnaires out of the 207 returned were incorrectly filled. Simple random sampling, a probability sampling technique was used in the study. Data analysis included descriptive statistics, correlation and regression analysis. The Cronbach’s Alpha co-efficient was used to measure reliability. The findings revealed that the majority of small businesses in Vryburg region of South Africa are market oriented. The findings further show that there is a positive relationship between market orientation and the performance of small business in the Vrburg region of South Africa. The study proposed the formalisation of small businesses, the development of strategic cultures as well as entrepreneurship and business management training for small business owners and managers.